PENGEMBANGAN PRODUKTIVITAS MASYARAKAT PEDESAAN MELALUI PENDIDIKAN LIFE SKILLS BERBASIS SUMBER DAYA LOKAL (Studi Kasus Di Desa Tamantirto Kasihan Bantul) - Aiman, Umul; Sriwijaya, Bambang; Swasono, F. Didiet Heru (Universitas Negeri Yogyakarta, 2011)
Tamantirto Village is a village with a population of 728 categories of poor households (28.46%). To reduce the level of poverty which is done by providing knowledge and skills of local resource utilization in the community. Transfer of knowledge and technology conducted by extension, practice, creation of demonstration plots as well as comparative studies. Knowledge and presence will include fish farming, household waste management, recognition and processing of medicinal plants into instant beverage and syrups. The result is a rural communities of Tamantirto was service capable of freshwater fish culture technologies and conduct intensive cultivation with a pool tarp. Capable of processing organic waste into compost and liquid fertilizer and manage of inorganic waste. Rural communities recognize a variety of medicinal plants in the environment and can process them into instant beverages and syrups. Society has increased the quality of life of its environmental cleanliness and income